Pengaruh Kemandirian, Kerja Sama, Dan Kreativitas Siswa Terhadap Keberhasilan P5 Kelas VII SMPN 1 Sandai - dita indah cahya; dewi sulistiyarini; ratih widya nurcahyo (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study aims to determine the effect of independence, cooperation, and creativity on the success of the Pancasila Student Profile Strengthening Project (P5), both partially and simultaneously. The research was conducted at SMP Negeri 1 Sandai with a sample of 114 class VII students. The research approach used quantitative methods with a causal-comparative descriptive design and an ex post facto approach. Based on the results of descriptive statistical tests, prerequisite tests, and simple and multiple linear regression hypothesis tests, it was found that there was an effect of independence on the success of the P5 Project with a Sig. value of 0.001 < 0.05 (Ha accepted), there was an effect of cooperation on the success of the P5 Project with a Sig. value of 0.011 < 0.05 (Ha accepted), there was an effect of creativity on the success of the P5 Project with a Sig. value of 0.034 < 0.05 (Ha accepted), and there was a simultaneous effect of independence, cooperation, and creativity on the success of the P5 Project with an R value = 0.621 and R Square = 0.386, indicating a contribution of 38.6%, while 61.4% was influenced by other factors. These findings are important as educators can use them as a basis for enhancing student independence, cooperation, and creativity through P5 activities. Keywords: Cooperation; Creativity; Independence; Pancasila Student Profile Strengthening Project (P5)